Alkaline and thermostable polygalacturonase from Streptomyces halstedii ATCC 10897 with applications in waste waters - Ramírez Tapias, Yuly Andrea (2015)
Pectin degrading enzymes with polygalacturonase (PG) activity hydrolyze α-(1,4) glycosidic bonds of polysaccharides present in higher plants. In the current study one hundred bacterial strains were screened for extracellular PG activity using an inductive culture medium. Optimization of fermentation conditions for Streptomyces halstedii ATCC 10897 was conducted using experimental designs. The maximum enzymatic activity obtained was 3.489. U/mL and 98.0% of viscosity reduction after 12. h of fermentation using soy peptone as unique source of carbon and nitrogen. PG from S. halstedii ATCC 10897 showed high thermal stability, an approximate molecular weight of 48. kDa and its optimum conditions for catalytic reaction were 50. °C and pH 12.0. This study reveals that alkaline PG is a useful enzyme for depectinization in alkaline pulping mill and papermaking waste waters. halstedii produces extremely alkalophilic polygalacturonase (48kDa) at 12h.